Urban Planning 4.0: geolocated data from social networks for urban intervention - Serrano-Estrada, Leticia; Nolasco-Cirugeda, Almudena; Martí Ciriquián, Pablo (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
There are many different approaches emerging from urban research which recognize the great potential of social media data for describing, diagnosing, predicting, and prescribing decision-making processes in the field of urban planning and urban regeneration. Numerous methods and sources have been widely explored to enrich our knowledge of cities. However, only few and/or scarcely disseminated urban agendas, planning instruments, projects and interventions have explicitly been based on the findings obtained from the analysis of geolocated social media data. In this sense, this research explores the possibility of integrating this layer of information into urban diagnoses to inform the formulation of urban planning documents and agendas in the Spanish context. A selection of planning instruments and their classification in the context of these two different kinds of intervening in the city are discussed, suggesting the possible inclusion of data from specific social media platforms in the specific areas of these regulations. This paper illustrates the practical application of these data as a main source for the development of diagnoses and intervention proposals by examining the experience of three specific case studies.